The Effect of Electronic Health Record Burden on Pediatricians' Work–Life Balance and Career Satisfaction - Frintner, Mary Pat; Kaelber, David C.; Kirkendall, Eric S.; Lourie, Eli M.; Somberg, Chloe A.; Lehmann, Christoph U. (Applied Clinical Informatics, 2021)
Objectives To examine pediatricians' perspectives on administrative tasks including electronic health record (EHR) documentation burden and their effect on work–life balance and life and career satisfaction.Methods We analyzed 2018 survey data from the American Academy of Pediatrics (AAP) Pediatrician Life and Career Experience Study (PLACES), a longitudinal cohort study of early and midcareer pediatricians. Cohorts graduated from residency between 2002 and 2004 or 2009 and 2011. Participants were randomly selected from an AAP database (included all pediatricians who completed U.S. pediatric residency programs). Four in 10 pediatricians (1,796 out of 4,677) were enrolled in PLACES in 2012 and considered participants in 2018. Data were weighted to adjust for differences between study participants and the overall population of pediatricians. Chi-square and multivariable logistic regression examined the association of EHR burden on work–life balance (three measures) and satisfaction with work, career, and life (three measures). Responses to an open-ended question on experiences with administrative tasks were reviewed.Results A total of 66% of pediatrician participants completed the 2018 surveys (1,192 of 1,796; analytic sample = 1,069). Three-fourths reported EHR documentation as a major or moderate burden. Half reported such burden for billing and insurance and 42.7% for quality and performance measurement. Most pediatricians reported satisfaction with their jobs (86.7%), careers (84.5%), and lives (66.2%). Many reported work–life balance challenges (52.5% reported stress balancing work and personal responsibilities). In multivariable analysis, higher reported EHR burden was associated with lower scores on career and life satisfaction measures and on all three measures of work–life balance. Open-ended responses (n = 467) revealed several themes. Two predominant themes especially supported the quantitative findings—poor EHR functionality and lack of support for administrative burdens.Conclusion Most early to midcareer pediatricians experience administrative burdens with EHRs. These experiences are associated with worse work–life balance including more stress in balancing responsibilities and less career and life satisfaction.
Keywords: electronic health record; work–life balance; satisfaction